(untitled) (Journal of Asian Development Studies, 2015)
In this study, we aim to investigate causation linkage between international trade and economic growth in terms of export-led growth (ELG) hypothesis for Brazil, Russia, India, China, South Africa and Turkey. The empirical results obtained from frequency domain test suggest that export-led growth hypothesis is valid in Turkey, China, Brazil and Russia in different time frequencies. On the other hand, import-led growth hypothesis is valid in India and South Africa.